2020
DOI: 10.1007/s13201-019-1138-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of TiO2 and ZnO nanoparticles immobilized on clay in wastewater treatment: a review

Abstract: Increase in industrial and anthropogenic activities leads to a decline in water quality. This necessitates the need for the removal of contaminants from industrial and domestic wastewater. Clay minerals are naturally abundant and non-toxic materials that found to be useful for remediation of emerging contaminants from wastewater. This review paper presents an insight into clay, the simplest material (in solgel techniques) for the synthesis of TiO 2 and ZnO, mechanisms of their reactions, analytical techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(75 citation statements)
references
References 179 publications
(104 reference statements)
2
62
0
Order By: Relevance
“…Owing to great surface properties and the reactivity of these nanomaterials, inhibition of pathogens in water could be done easily [158]. Nanomaterials based on Ag, CuO, ZnO, TiO 2 , polymeric NPs and CNTs have been investigated for the disinfection of wastewater [159][160][161][162][163][164]. Among the metal NPs, copper (Cu) NPs are some of the most effective and potent antimicrobial agents.…”
Section: Disinfection and Pathological Controlmentioning
confidence: 99%
“…Owing to great surface properties and the reactivity of these nanomaterials, inhibition of pathogens in water could be done easily [158]. Nanomaterials based on Ag, CuO, ZnO, TiO 2 , polymeric NPs and CNTs have been investigated for the disinfection of wastewater [159][160][161][162][163][164]. Among the metal NPs, copper (Cu) NPs are some of the most effective and potent antimicrobial agents.…”
Section: Disinfection and Pathological Controlmentioning
confidence: 99%
“…Beside the optical behavior linked to the change in refractive index, the nanostructured materials obtained by BCPs self-assembly and SIS exhibit interesting photoemission properties. Particular attention was paid to the electro- and photo-luminescence of nanostructures based on ZnO, a biocompatible and non-toxic material [ 79 ] with a wide range of potential applications in photonics [ 48 , 80 ], solid-state devices [ 81 ], gas sensors [ 82 ], water treatment [ 83 ] and biosensors [ 84 ].…”
Section: Control Of the Materials’ Functional Properties By Sismentioning
confidence: 99%
“…One study indicated that a nanoparticle TiO 2 -based photoelectrocatalytic process has high potential to be utilized as an appropriate treatment method for pharmaceutical effluents containing cefotaxime antibiotics [37]. One of the most important problems of this process is recycling of nanoparticles, which can be addressed by doping and codoping of metal oxide nanomaterials, immobilization of nanoparticles on appropriate matrices, and nano-based filters through the combination of clay/ZnO nanocomposites [38,39].…”
Section: Effect Of the Catalyst Dosesmentioning
confidence: 99%